1974
DOI: 10.1136/jech.28.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of poisoning in a developing agricultural country

Abstract: Four hundred and seventy-two cases of poisoning were seen over a two-year period in Kandy, Ceylon. The overall mortality was 23 7 %. The pattern of poisoning was different from that in western countries in that 49 8 % of the cases weie due to insecticide poisoning and only 10 7 % were due to drugs, including barbiturates. Insecticides accounted for 73.2% and drugs for only 4 5% of the 112 fatal cases. Of the fatal cases 51'7 % were between the ages of 20 and 40 years and only 6 2% were over 50 years. The wasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The reported rates of non-fatal self-poisoning, either by pesticide ingestion, or by ingestion of any type of poison, increased in the three decades leading up to the turn of the century. In 1971–2 the reported rate of non-fatal self-poisoning (by any poison) was 26.2 per 100,000 (Kandy region)[18], whereas in 2002 it was 315 per 100,000 (Galle region) (Table 3) [8]. However except for one study [12], all reported self-poisoning rates were for specific regions in Sri Lanka rather than for the population of the country as a whole.…”
Section: Resultsmentioning
confidence: 99%
“…The reported rates of non-fatal self-poisoning, either by pesticide ingestion, or by ingestion of any type of poison, increased in the three decades leading up to the turn of the century. In 1971–2 the reported rate of non-fatal self-poisoning (by any poison) was 26.2 per 100,000 (Kandy region)[18], whereas in 2002 it was 315 per 100,000 (Galle region) (Table 3) [8]. However except for one study [12], all reported self-poisoning rates were for specific regions in Sri Lanka rather than for the population of the country as a whole.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] Reports available from certain Asian (Pakistan and SriLanka) and African countries (Uganda) describe organophosphates (crop sprays) and drugs as the commonly abused toxic substances with reported mortality rates varying from 2.0% to 2.1%. [11][12][13] The mortality/morbidity in any case of acute poisoning depends upon number of factors such as nature of poison, dose consumed, level of available medical facilities and the time of interval between intakes of poison and arrival at hospital, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Murphy (1954) reported that from 1940 to 1952, Hindus in Sri Lanka had a suicide rate of 7.7 while Muslims had a suicide rate of 5.6. Senewiratne and Thambipillai (1974) reported an excess of Sinhalese (primarily Buddhists) and a deficit of both Tamils (primarily Hindus) and Muslims in a mixed sample of completed and attempted suicides from the district of Kandy in the years of 1970 to 1971. Meer (1976) presented data for the suicide rates of ''Indians'' in Durban (South Africa) for 1940-1960, but Meer did not distinguish from which country in the Indian subcontinent the ''Indians'' came.…”
Section: Suicide Rates By Religion Within Nationsmentioning
confidence: 98%